Emergent Goal‐Anticipatory Gaze in Infants via Event‐Predictive Learning and Inference. Issue 8 (11th August 2021) - Gumbsch, Christian; Adam, Maurits; Elsner, Birgit; Butz, Martin V.
Abstract: From about 7 months of age onward, infants start to reliably fixate the goal of an observed action, such as a grasp, before the action is complete. The available research has identified a variety of factors that influence such goal‐anticipatory gaze shifts, including the experience with the shown action events and familiarity with the observed agents. However, the underlying cognitive processes are still heavily debated. We propose that our minds (i) tend to structure sensorimotor dynamics into probabilistic, generative event‐predictive, and event boundary predictive models, and, meanwhile, (ii) choose actions with the objective to minimize predicted uncertainty. We implement this proposition by means of event‐predictive learning and active inference. The implemented learning mechanism induces an inductive, event‐predictive bias, thus developing schematic encodings of experienced events and event boundaries. The implemented active inference principle chooses actions by aiming at minimizing expected future uncertainty. We train our system on multiple object‐manipulation events. As a result, the generation of goal‐anticipatory gaze shifts emerges while learning about object manipulations: the model starts fixating the inferred goal already at the start of an observed event after having sampled some experience with possible events and when a familiar agent (i.e., a hand) is involved. Meanwhile, the model keeps reactively tracking an unfamiliar agent (i.e., a mechanical claw) that is performing the same movement. We qualitatively compare these modeling results to behavioral data of infants and conclude that event‐predictive learning combined with active inference may be critical for eliciting goal‐anticipatory gaze behavior in infants.